2003
DOI: 10.1016/s1567-7249(03)00060-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1,4-dihydropyridine derivatives (cerebrocrast, gammapyrone, glutapyrone, and diethone) on mitochondrial bioenergetics and oxidative stress: a comparative study

Abstract: The potential protective action of 1,4-dihydropyridine derivatives (cerebrocrast, gammapyrone, glutapyrone, and diethone) against oxidative stress was assessed on mitochondrial bioenergetics, inner membrane anion channel (IMAC), Ca 2þ -induced opening of the permeability transition pore (PTP), and oxidative damage induced by the oxidant pair adenosine diphosphate (ADP)/Fe 2þ (lipid peroxidation) of mitochondria isolated from rat liver. By using succinate as the respiratory substrate, respiratory control ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
4
16
0
Order By: Relevance
“…This assumption is supported by comparing the results obtained in this study (Figs. 2-4) with the results of identical experiments previously performed with OSI-1212 (cerebrocrast) [16], clearly showing that, at high concentrations (>25 M), like its isomer OSI-3802, has a significant effect on mitochondrial bioenergetics by affecting inner mitochondrial membrane permeability to cations. The influence of 3,5-dialkoxycarbonyl chain length of the 1,4-dihydropyridines on mitochondrial bioenergetics was previously reported for other DHP derivatives.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This assumption is supported by comparing the results obtained in this study (Figs. 2-4) with the results of identical experiments previously performed with OSI-1212 (cerebrocrast) [16], clearly showing that, at high concentrations (>25 M), like its isomer OSI-3802, has a significant effect on mitochondrial bioenergetics by affecting inner mitochondrial membrane permeability to cations. The influence of 3,5-dialkoxycarbonyl chain length of the 1,4-dihydropyridines on mitochondrial bioenergetics was previously reported for other DHP derivatives.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, the calcium antagonist foridone (ryodipine, PP-1466), which possesses the same substituent in the position 4 as OSI-1212 (cerebrocrast) and its analogues studied herein, improves mitochondrial bioenergetics in the isolated rat mitochondria from the infarct zone of the heart as well as from relatively undamaged zone [14]. Moreover, we have shown OSI-1212 (cerebrocrast) ability to interact with rat skeletal, neuronal and hepatic mitochondria [15,16], to incorporate into mitochondrial membranes and to induce lipid membrane organization changes [17]. Mitochondria have also been considered as an essential intracellular target for OSI-1212 (cerebrocrast) neuroprotective actions [18,19].…”
Section: Introductionmentioning
confidence: 93%
“…Recent data obtained from studies on isolated liver mitochondria are in good agreement with our results, since they have demonstrated that only lipophilic cerebrocrast but not amino acid-containing DHPs blocks the inner membrane anion channel, K þ /H þ antiporter, and partially prevented Ca 2þ -induced opening of the mitochondrial permeability transition pore. 28 One may suggest that cerebrocrast-induced neuroprotection in vivo experiments can be explained to a great extent by its regulatory properties at the level of mitochondrial processes. Mitochondria probably cannot be considered as the crucial target for glutapyrone and tauropyrone.…”
mentioning
confidence: 99%
“…53 It was shown that cerebrocrast inhibited isolated rat liver mitochondria inner membrane anion channels and partially prevented Ca-induced opening of the mitochondrial PTP, thereby preventing excessive calcium accumulation inside mitochondria as well as inhibiting Cl À transport in the mitochondria. 54 It is As shown in a recent investigation (unpublished data), cerebrocrast at concentrations of 10 and 100 nM significantly inhibited T-type calcium channels. The increase of T-type calcium channel activity evoked a thalamo-cortical dysfunction.…”
Section: Discussionmentioning
confidence: 58%